An Evaluation of the Progressive Supranuclear Palsy Speech/Language Variant. Issue 6 (29th May 2019) - Whitwell, Jennifer L.; Stevens, Chase A.; Duffy, Joseph R.; Clark, Heather M.; Machulda, Mary M.; Strand, Edythe A.; Martin, Peter R.; Utianski, Rene L.; Botha, Hugo; Spychalla, Anthony J.; Senjem, Matthew L.; Schwarz, Christopher G.; et al.
ABSTRACT: Background: The Movement Disorder Society clinical criteria for progressive supranuclear palsy (PSP) provide a framework for assessing the presence/severity of clinical symptoms and define a speech/language variant of PSP. Objectives: To evaluate the clinical criteria in a cohort of speech/language patients with longitudinal follow‐up. Methods: A total of 52 patients presenting with progressive apraxia of speech and/or agrammatic aphasia were followed longitudinally for up to 6 visits with clinical assessments and magnetic resonance imaging. We assessed oculomotor, postural instability, and akinesia diagnostic levels and determined whether patients met criteria for possible PSP‐speech/language or probable PSP at each visit. Kaplan‐Meier curves assessed time‐to‐event probabilities according to age. Statistical parametric mapping and midbrain volume were assessed according to disease progression. Results: Few PSP symptoms were observed early in the disease, with oculomotor abnormalities and falls first observed 2 years after onset. Falls were more common than vertical supranuclear gaze palsy. Bradykinesia and rigidity commonly developed but axial was rarely greater than appendicular rigidity. During follow‐up, 54% met criteria for possible PSP‐speech/language, 38% for probable PSP‐Richardson's syndrome, and 38% for probable PSP‐parkinsonism, most commonly 6 to 6.9 years after onset. The probability of developing PSP was greater when onset was at an age older than 70 years. Patients who progressed to probable PSP had more parkinsonism and oculomotor impairment at baseline and greater midbrain atrophy when compared with those who did not develop probable PSP. Conclusions: Symptoms typical of PSP commonly develop in patients presenting with a progressive speech/language disorder. Older age appears to be an important prognostic factor in these patients.